Musculoskeletal Symptoms during COVID-19 Pandemic in a Tertiary Care Hospital in South India - Vetrivel Chezian Sengodan; Marimuthu Sivagnanam; Surendhar Rathinasamy; Ranjithkumar Selvaraj (Journal of Orthopedics and Joint Surgery, 2022)
Background: The symptoms of COVID-19 include fever, myalgia, arthralgia, fatigue, headache, sore throat, dry cough, anosmia, ageusia/dysgeusia, and progression to viral pneumonia. Musculoskeletal symptoms such as fatigue, myalgia, and arthralgia are common COVID-19 symptoms, but their prevalence has not yet been systematically investigated. Hence, our study aims to know the incidence of musculoskeletal symptoms in COVID-19 infection and their relationship between comorbidities like diabetes and hypertension. Methods: In our study, 1053 COVID-19 infected patients confirmed by the RT-PCR method were included. For all the patients in our study, detailed history of musculoskeletal symptoms and comorbidities were collected. Basic investigations were done for all the patients and appropriate treatment was given. The patients were followed up for persistence of musculoskeletal symptoms after discharge from the hospital. Results: During COVID-19 infection, knee joint pain was present among 251 patients (23.8%), generalized myalgia in 147 patients (14%) and 40 patients (3.8%) had both knee joint pain and generalized myalgia. In these patients, during the post-COVID follow-up, 198 patients had persistent knee joint pain, 100 patients had persistence of generalized myalgia and 38 patients had persistence of both knee pain and myalgia, whereas 19 patients developed knee joint pain and one patient developed generalized myalgia after COVID-19 infection. From our study, it is evident that the musculoskeletal symptoms are more during COVID-19 infection than during the pre-COVID period. Compared with pre-COVID status, generalized myalgia is more during the post-COVID follow-up period. This was analyzed with Cochran's Q test and was found to be statistically significant (p < 0.05). Conclusion: Our study showed an increased incidence of musculoskeletal symptoms during and after COVID-19 infection, the most common being generalized myalgia followed by knee joint pain. In patients with comorbidities like diabetes and hypertension, it is evident that musculoskeletal symptoms like knee joint pain and generalized myalgia are increased during COVID-19 infection.